Desafios e perspectivas da educação do campo em Alegre/ES: análise da efetividade do fundeb permanente como instrumento de financiamento para promoção da equidade e justiça social - Oliveira, Vanusia Azevedo Aguiar de (2024)
This study critically examines the implementation of the Fund for the Maintenance and Development of Basic Education and the Valorization of Education Professionals (Permanent FUNDEB) in Rural Education in Alegre/ES, from a perspective of equity and social justice. The objective of this research is to analyze the challenges and opportunities related to the implementation of Permanent FUNDEB in rural schools in Alegre/ES, with the aim of promoting equity and social justice and supporting the development of more effective public policies for rural communities in the municipality. The research covers the period from 2007 to 2023, allowing for a comparative analysis of the former FUNDEB and the Permanent FUNDEB, both in relation to rural education and their implications for equity and social justice. The methodology employed a qualitative approach, utilizing documentary research, case study, bibliographic review, and data collection through semi-structured interviews and document analysis. Data were analyzed using content analysis techniques. The results indicate that rural schools in Alegre/ES face significant structural deficiencies, including urgent needs for renovation and repairs of physical facilities. There is also a shortage of resources and pedagogical materials tailored to the specific needs of rural schools, and access to educational technologies is rare or inadequate. Pedagogical support is insufficient, with a lack of continuous professional development programs that address the particularities of rural education. The municipality lacks a specific educational plan for its rural schools and often treats them as extensions of urban zones. Additionally, Permanent FUNDEB has not effectively promoted equity and social justice in rural education in Alegre/ES, leaving rural communities marginalized in terms of the conditions necessary for quality education. These communities demand recognition of their unique identity and the development of educational policies that value their history, culture, and rights. There is also a lack of knowledge among teachers and the community regarding the resources available through Permanent FUNDEB, as well as difficulties in data management by the FUNDEB Monitoring and Social Control Council (CACS-FUNDEB). Fear of school closures remains a pressing challenge, particularly given that 57 rural schools were closed between 2013 and 2024. In conclusion, there is an urgent need to develop public policies that strengthen the cultural identity and value the knowledge of rural communities, with a focus on equity and social justice.